(untitled) (Journal of the College of Basic Education, 2026)
The purpose of the study is to categorize the character types that present in The Glass Menagerie and Long Day’s Journey into Night. It analyzes how these character types embody and convey the social issues and central themes of these plays within the topic of modern American drama. These two plays clarify the evolution of character-driven narrative in American drama and explore enduring themes of family, identity, and societal pressures in a modern context. The study employs a qualitative approach. Thematic analysis is also used to analyze the study objectives and elicit the results. Its analysis is primarily based on dramatic theory, including Archetypal Theory, which helps understand recurring character patterns and their symbolic meanings in modern American drama. The main results showed that Tennessee Williams’s The Glass Menagerie features characters imbued with nostalgia, vulnerability, and the tension between reality and dreams, while Eugene O’Neill’s Long Day’s Journey into Night features rawer and psychologically charged characters struggling with illness, addiction, and regret. Williams’ characters inhabit fragile fantasies, while O’Neill’s characters face harsh realities. Future research could reveal comparative analyses of characterization by other important American playwrights.